The moderating effect of parental mediation in the longitudinal associations among cyberbullying, depression, and self-harm among Chinese and American adolescents - Wright, Michelle F. (Frontiers in Psychology, 2024)
For full guidelines please refer to Author Guidelines Researchers have concentrated on identifying factors that might mitigate the negative consequences associated with cyber victimization. One key factor that has garnered significant attention is parental mediation in adolescents' digital technology usage and its role in reducing the risk of cyber victimization. Additionally, the buffering effects of parental mediation on the longitudinal associations among cyberbullying victimization, depression, and self-harm have been underexplored, especially cross-cultural investigations of such effects. To address this gap, the present study examined the role of parental mediation in buffering against depression and self-harm, both measured one year later, associated with cyberbullying victimization among 463 Chinese (49% female) and 445 American (52% female) eighth graders (ages 13-15). The findings revealed that Chinese adolescents reported higher levels of parental mediation across a one-year period compared to their American counterparts. High levels of parental mediation were associated with a more negative relationship between cyberbullying victimization, depression, and self-harm for both Chinese and American adolescents, but these effects were stronger for Chinese adolescents. These results are discussed in the context of cultural values and how these values shape the role of adults in adolescents' lives. parental mediation of adolescents' technology use, which is believed to guard against the negative consequences of digital technology usage (Abelman, 2006;Nikken & Jansz, 2006;Sciacca et al., 2022). Research shows that inadequate parental supervision is linked to cyberbullying and exposure to inappropriate content such as pornography (Fong-Ching Chang et al., 2021;Lwin et al., 2008; Mesch, 2009). Consequently, there is a growing focus on understanding how parents' mediation of adolescents' technology use can buffer against these negative outcomes.